Determinants of fluid milk purchasing sources in Ethiopia - Kuma, B.; Baker, Derek; Getnet, Kindie; Kassa, B. (2010)
This study investigated main determinants affecting fluid milk purchasing sources of households in Wolaita zone, Ethiopia. From the collected household survey data, a multinomial logit model was estimated to analyze households„ choices among processed, unprocessed and both processed-unprocessed fluid milk sources within the utility maximization framework. The results indicate that households with at least a child under the age of six, who rejects the statement „price of processed fluid milk is expensive compared with unprocessed fluid milk., indigenous or native resident type and no order from doctor to consume fluid milk were more likely to purchase processed-unprocessed over processed fluid milk. Household heads whose education levels are formal and higher, lower income, who accept the statement „price of processed fluid milk is expensive compared with unprocessed fluid milk., indigenous or native resident type, no order from doctor to consume fluid milk and reject the statement processed fluid milk fattens children were more likely to purchase unprocessed fluid milk over processed. Households without child under the age of six, lower income level and rejects the statement „processed fluid milk fattens their children. were more likely to purchase unprocessed fluid milk over processed-unprocessed. The implications of these results for dairy value chain actors in developing countries are discussed.